2004
DOI: 10.1051/animres:2004033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of constant dietary energy supply during late gestation and early lactation on performances of prolific D’man ewes

Abstract: -A total of 42 prolific D'man ewes were used to study the effect of the dietary energy supply on their performances during the last 45 days of pregnancy and the first 60 days of the suckling phase. The ewes were fed 1 kg of hay and supplemented with either 200 (treatment L), 570 (treatment M) or 840 g (treatment H) of a barley and soyabean-based concentrate. The proportion of soyabean was adjusted so that the crude protein (CP) content of the three diets was similar (120 g CP·kg -1 ). The energy contents of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The results of the interaction effect showed no significant difference in lambs body weight gain at different interval after lambing (Table 12) These results agreed with Mahouachi et al (2004), who reported that average daily growth rates at 30 days of age was affected by the diets energy level of their dams which fed 1 kg of hay and supplemented with either 200 (treatment L), 570 (treatment M) or 840 g (treatment H) of concentrate during late early lactation. These results are in contrast with Sultana et al (2012) who found that daily weight gain of kids of Black Bengal goats did not differ significantly between groups given 150, 200, 250 and 300 g concentrate mixture with ad libitum green grasses.…”
Section: Itemssupporting
confidence: 85%
“…The results of the interaction effect showed no significant difference in lambs body weight gain at different interval after lambing (Table 12) These results agreed with Mahouachi et al (2004), who reported that average daily growth rates at 30 days of age was affected by the diets energy level of their dams which fed 1 kg of hay and supplemented with either 200 (treatment L), 570 (treatment M) or 840 g (treatment H) of concentrate during late early lactation. These results are in contrast with Sultana et al (2012) who found that daily weight gain of kids of Black Bengal goats did not differ significantly between groups given 150, 200, 250 and 300 g concentrate mixture with ad libitum green grasses.…”
Section: Itemssupporting
confidence: 85%
“…Under favorable breeding conditions, this breed reaches a mean post-weaning weight (age at 180 days) of 37.08 ± 5.16 kg (37.71 ± 5.65 kg in the male and 36.38 ± 4.62 kg in the female). The weight at birth of lambs in this breed is largely important compared to other breeds : 3.5 kg in OuledDjellal (IANOR, 2007), 4 kg in Rembi (IANOR, 2013), 3.1 kg in Hamra (IANOR, 2007), 2.60 kg in the D'man breed (Mahouachi et al,2004), 3.7 kg in the Sardi breed (Boujenane et al,2001), 3, 72 kg in the Timahdite breed (Boujenane and Kansari, 2005), 2.8 kg in Ile-de-France (Boujenane, 2005) and comparable to that of the Moroccan breed Boujaâd : 4.95 kg (El Amiri et al, 2010), of the Awassi breed from the Middle East : 4.3 kg (Kridli et al,2006), the Mexican Blackbelly breed : 4.5 kg (Herrera-Alarcón et al,2007). The growth performance achieved by lambs of the Tazegzawt breed is comparable to that of other local breeds in Algeria.…”
Section: Weight and Growth Ability Of Lambsmentioning
confidence: 97%